Immobilized Catecholamine and Cocaine Effects on Contractility of Cardiac Muscle - Venter, J. Craig (1973)
Isoproterenol, norepinephrine, and epinephrine covalently bound to glass beads exert a positive inotropic effect on isometrically contracting papillary muscles from cats. Immobilized isoproterenol maintains increases in force and velocity of contraction for more than 5 hr. 1 μM Cocaine potentiates the action of immobilized norepinephrine, isoproterenol, and epinephrine, but not of isoproterenol in solution. The data presented indicate that the effects of immobilized catecholamines are not due to their coming off the glass. The effects observed with cocaine and immobilized catecholamines are not altered by prior treatment of the muscle with reserpine. These results suggest that the major site of catecholamine action is on receptors located on the extended surface of myocardial cells and a post-junctional site for cocaine potentiation.